Blood circulation in the ascidian tunicate Corella inflata (Corellidae) - Konrad,Michael W. (PeerJ, 2016)
The body of the ascidian tunicate Corella inflata is relatively transparent. Thus, the circulatory system can be visualized by injecting high molecular weight fluorescein labeled dextran into the heart or the large vessels at the ends of the heart without surgery to remove the body wall. In addition, after staining with neutral red, the movement of blood cells can be easily followed to further characterize the circulatory system. The heart is two gently curved concentric tubes extending across the width of the animal. The inner myocardial tube has a partial constriction approximately in the middle. As in other tunicates, the heart is peristaltic and periodically reverses direction. During the branchial phase blood leaves the anterior end of the heart by two asymmetric vessels that connect to the two sides of the branchial basket. Blood then flows in both transverse directions through a complex system of ducts in the basket into large ventral and dorsal vessels which carry blood back to the visceral organs in the posterior of the animal. During the visceral phase blood leaves the posterior end of the heart in two vessels that repeatedly bifurcate and fan into the stomach and gonads. Blood velocity, determined by following individual cells in video frames, is high and pulsatory near the heart. A double peak in velocity at the maximum may be due to the constriction in the middle of the heart tube. Blood velocity progressively decreases with distance from the heart. In peripheral regions with vessels of small diameter blood cells frequently collide with vessel walls and cell motion is erratic. The estimated volume of blood flow during each directional phase is greater than the total volume of the animal. Circulating blood cells are confined to vessels or ducts in the visible parts of the animal and retention of high molecular weight dextran in the vessels is comparable to that seen in vertebrates. These are characteristics of a closed circulatory system.
Keywords: Heart; Branchial basket; Blood velocity; Closed circulation; Blood circulation; Pharynx; Closed